Neural Stem Cell or Human Induced Pluripotent Stem Cell-derived GABA-ergic Progenitor Cell Grafting in an Animal Model of Chronic Temporal Lobe Epilepsy - Upadhya, Dinesh (Curr Protoc Stem Cell Biol, 2016)
Grafting of neural stem cells (NSCs) or GABA-ergic progenitor cells (GPCs) into the hippocampus could offer an alternative therapy to hippocampal resection in patients with drug-resistant chronic epilepsy, which afflicts >30% of temporal lobe epilepsy (TLE) cases. Multipotent, self-renewing NSCs could be expanded from multiple regions of the developing and adult brain, human embryonic stem cells (hESCs), and human induced pluripotent stem cells (hiPSCs). On the other hand, GPCs could be generated from the medial and lateral ganglionic eminences of the embryonic brain and from hESCs and hiPSCs. To provide comprehensive methodologies involved in testing the efficacy of transplantation of NSCs and GPCs in a rat model of chronic TLE, NSCs derived from the rat medial ganglionic eminence (MGE) and MGE-like GPCs derived from hiPSCs are taken as examples in this unit. The topics comprise description of the required materials, reagents and equipment, methods for obtaining rat MGE-NSCs and hiPSC-derived MGE-like GPCs in culture, generation of chronically epileptic rats, intrahippocampal grafting procedure, post-grafting evaluation of the effects of grafts on spontaneous recurrent seizures and cognitive and mood impairments, analyses of the yield and the fate of graft-derived cells, and the effects of grafts on the host hippocampus.